2020
DOI: 10.5603/arm.2019.0060
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Treatment Standards in Idiopathic Pulmonary Fibrosis in the Era of Antifibrotic Drugs in Poland: A Real-World Practice Survey

Abstract: Introduction: Currently, only two drugs have been shown to modify the inevitable natural history of idiopathic pulmonary fibrosis (IPF). Changes in the reimbursement policy for antifibrotic drugs in Poland have led to the availability of pirfenidone from January 2017 and nintedanib from March 2018 for the treatment of Polish patients with IPF. This study aimed to evaluate the possible changes and shortcomings in the clinical practice standards in IPF in the era of access to antifibrotic therapy in Poland. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recently, changes in the reimbursement policy for antifibrotics in Poland have led to the wider availability of pirfenidone since January 2017 for the treatment of Polish patients with IPF [34]. The drug has become available in the frame of therapeutic program refunded by the NHF for patients with the mild-to-moderate disease based on the inclusion criteria similar to those used for the phase III pirfenidone RCT, namely the ASCEND study [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, changes in the reimbursement policy for antifibrotics in Poland have led to the wider availability of pirfenidone since January 2017 for the treatment of Polish patients with IPF [34]. The drug has become available in the frame of therapeutic program refunded by the NHF for patients with the mild-to-moderate disease based on the inclusion criteria similar to those used for the phase III pirfenidone RCT, namely the ASCEND study [5].…”
Section: Discussionmentioning
confidence: 99%
“…Both national Polish and European findings confirm the urgent need for improvement in the area of ILD diagnosis. Multidisciplinary discussion (MDD), involving at minimum a pulmonologist and a radiologist with expertise in the differential diagnosis of ILD, is required to ensure an accurate diagnosis [ 12 , 21 ]. MDD is critical for the diagnosis of IPF and other ILD, especially when the HRCT patterns and clinical workup do not provide a clear diagnosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the first ILD workup performed at the local respiratory center was a reason for an initial delay of an accurate IPF diagnosis. A recent survey undertaken in a representative group of Polish pulmonologists showed that only 63% of them routinely work with an ILD expert radiologist for the differential diagnosis of ILD [ 21 ]. In the authors' opinion, the formation of experienced multidisciplinary teams in Polish respiratory centers involved in ILD diagnosis and management should become a priority as long as IPF diagnostic standards are considered.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] It is characterized by nonproductive cough and exertional breathlessness. [ 2 3 4 ] The median survival of patients with IPF has been reported to range from 2.5 to 3.5 years. [ 2 5 ]…”
mentioning
confidence: 99%